Employment experiences of post graduate students in KwaZulu-Natal: An intersection of qualifications and employability in the labor market - Ndebele, N.C.; Ndlovu, J. (South African Journal of Higher Education, 2019)
The past decade has seen a sturdy increase in the literature on higher education and policy discourse on the absorption of graduates in the labor market. To understand students’, post graduate experiences, a case approach was adopted. Participants comprised of employed and unemployed students who were registered at the University of Zululand in 2016 particularly those who successfully completed their undergraduate degree in any South African tertiary institution. An empirical study shows that Graduates lack job market information and experience to enable them to undertake this arduous journey. Unemployment and under employment was found to be due to lack of certain personal attributes, serious skills mismatch and general lack of capability. The paper argues that there is a gap between qualifications and capability-employment in the labour market. Higher education institutions and industry should bridge this gap by emphasising on labour market needs, individual attributes and social inequalities in programme design.